PENGARUH RETURN ON ASSETS, RETURN ON EQUITY, EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR BEI - Sorongan, Fangky A. (FEB Universitas Sam Ratulangi Manado, 2019)
The purpose of this study is to analyse the impact of Return on Assets, Return on Equity, and Earning per Share against stocks in automotive companies listed on the Indonesia Stock Exchange. The data used in this study was obtained from the annual company financial statement data of the 2013-2016 period. The analytical techniques used in this study were the data regression panel. The results of the study using the fixed effect model found that Return on Assets had no significant effect on the stock price, while Return on Equity was negatively and significantly impacted by the share price and the Earning per Share have a positive and significant effecr towards the stock price.Keywords: fixed effect, profitabilitas, Return on Assets, Return on Equity, Earning per Share, harga saham